(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study examines the development of tourism in Bandung during the early twentieth century under Dutch East Indies colonial rule. The emergence of tourism was driven by the rise of leisure consciousness among Europeans after the Industrial Revolution, which fostered a middle-class recreational culture. Capitalist travel companies capitalized on this trend by offering tour packages to the colonies, including the Dutch East Indies. In Bandung, tourism expanded alongside the colonial modernization of the tropical city, which aimed to enhance European living standards. Using a historical-descriptive method, this research draws on tourist booklets, travel accounts, and colonial reports as primary sources, supported by relevant scholarly literature. The findings indicate that Bandung became a major tourist destination due to its cool climate, scenic landscape, and its carefully constructed image as a “modern tropical city.” Promotional media—especially illustrated booklets and international exhibitions— reinforced Bandung’s branding as the “Paris of Java.” Two main forms of tourism emerged: natural tourism focused on mountains and valleys, and urban tourism showcasing modern architecture and leisure amenities. Ultimately, Bandung’s tourism reflected both the capitalist commodification of leisure and the colonial imagination of the “exotic East,” positioning the city as a symbolic representation of modern colonial urban life and the interplay of power, culture, and space.